EVALUASI KEBUTUHAN ENERGI LISTRIK KECAMATAN LUBUK BASUNG TERKAIT PEMBANGUNAN PLTM LUBUK SAO DI KABUPATEN AGAM MENGGUNAKAN METODA REGRESI LINEAR PADA SPSS - Nurhatisyah Nurhatisyah; Valdi Rizki Yandri; Zaid Binggafar (Situs resmi ITP Press, 2014)
Renewable energy use is a primary needs because high population increases will incline electrical energy demand. Noticeably, one kind of renewable energy application is in Mini Hydro Power Plant Lubuk Sao to supply electrical power to Lubuk Basung sub district in Agam District. This power plant with capacity 2.6 MW uses water waste from Maninjau power plant and will be operated in year 2015. Furthermore, electrical demand in Lubuk Basung will incline because of the movement of Agam government central to this area. In order to prevent the energy deficit in Lubuk Basung, it is needed the electrical forecasting method, i.e. SPSS Linear Regression Method. Based on the calculation of peak load inLubuk Basung, this area requires 44.65 MW electrical power in year 2016. It means the electrical power supplyfrom Mini hydro power plant Lubuk Sao in value 2.6 MW can supply apart of electrical demand in LubukBasung and the rest, i.e. 42.05 MW should be supplied by Maninjau power plant with the estimation of electricalpower form Maninjau power plant will be 58.05 MW in 2016. The rest electrical power in value 16 MW can betransmitted to other areas